«Halyk Bank» the Analysis of financial stability of the joint-stock company as the tool for increase in system effectiveness of internal audit - Lambekova, A.N.; Nurgaliyeva, A.M. (BUKETOV BUSINESS REVIEW, 2017)
The banking system is an important component of the market economy. Aimed at improving the quality of effective management of the bank and its most important functions on the basis of improving governance, stability of domestic banks in the second level of the banking system, respectively, lead to the development of the entire economy.This article shows an analysis of the financial performance of the internal audit of banks of the second level of correlation - regresionnym mathematical method. In the analysis as an important factor in performance of their own capital of commercial banks were taken. Because at the moment, capital adequacy is one of the most important tasks facing the second-tier banks in Kazakhstan. In connection with the increase in equity capital of JSC «Halyk Bank’s» creditworthiness, the financing of industrial enterprises, an increase of equity capital promotes the development of the national economy. The article shows the factors that influenced the change in equity of the dynamics of Halyk Bank for the period 2005–2015. Using stepwise regression selected influencing factors and, accordingly, they built three adequate regression models. As a result, to determine what factors affect the dynamics of change in equity of JSC «Halyk Bank».